Rancang Bangun Sistem Informasi Penjualan Dan Pembelian Koperasi Mahasiswa (Studi Kasus Koperasi Mahasiswa Universitas Negeri Surabaya) - Irfandi Agung Perdana; Bambang Hariadi; Tan Amelia (Jurnal Sistem Informasi Universitas Dinamika, 2012)
Cooperative State University student Surabaya is the type of business cooperatives engaged in the campus environment. Key business processes in the cooperative is selling and buying. Cooperative Surabaya State University students are constrained in clarifying the sales in detail, specifying the items expired, calculates sales records to determine the contribution of each member to member, to calculate changes in the cost of goods in the event of price changes at the time of the purchase process, and knowing the flow of goods in and out of card stock . Based on the description above, we need a system of buying and selling information on student cooperative. The system was built consisting of cash sales, print receipts cash sales, cash purchases, consignment purchases, purchases payable, consignment payment, accounts payable payments, print receipt consignment, master recap reporting, reporting cash sales, reporting a cash purchase, reporting, accounts payable, consignment reporting, card inventory, daily information, the information per member, and infomrasi per item. From the results of testing the sale and purchase of information systems in cooperative Surabaya State University students concluded that the system can run the business of selling and buying process, issuing reports and information required by the cooperative management students of the State University of Surabaya. Keywords: Cooperative Information Systems, Technology, Sales, Purchases.